Effects of Electronic Technology Antenatal Care (E-ANC) on Midwives and Pregnant Women during the COVID-19 Period - Nur, Rosmala; Radiah, St.; Aulia, Ulfa; Rahma Dwilarasati, Rahma; Patui, Nurhaya S.; Mantao, Elvaria; Hendra, Syaiful; Ngemba, Hajra Rasmita; Rusydi, Muh; Dominggo, Nenita P. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Pregnant women are considered as a risk group for exposure to COVID-19. Changes in their hormones and immune systems possibly influence their rate of infection by several viruses, including the coronavirus. This stresses the need to observe necessary precautions, by maintaining social distancing, avoiding crowds, and staying at home. Furthermore, the condition also influences the scope of pregnant women’s antenatal visits. AIM: The study aims to determine the effect of COVID-19 on antenatal visits by pregnant women. Furthermore, it seeks to ascertain the effect of electronic technology antenatal care (e-ANC) on the enhanced participation of midwives and pregnant women in antenatal care (ANC) (i.e., counseling, high-risk early detection on pregnancy, and monitoring of Hb and Fe tablets). Therefore, the impact COVID-19 on women’s reproductive health during the pandemic is also evaluated. METHODS: This research involved pre- and post-test experiments on 30 pregnant women and 20 midwives at areas around the Public Health Centers in Tinggiede and Marawola. A purposive sampling technique was adopted, and the results were analyzed using a paired t-test. RESULTS: The study showed discrepancies in the ANC visits of pregnant women before and after the COVID-19 lockdown period, with p < 0.00. Furthermore, there were also differences in midwife participation in counseling by p < 0.00, high-risk early detection on pregnancy by p < 0.001, Hb monitoring by p < 0.002, and provision of Fe tablets by p < 0.003 during the pandemic. Moreover, the pregnant women showed variations in the frequency of counseling by p < 0.00, high-risk early detection on pregnancy by p < 0.00, Hb monitoring by p < 0.002, and the provision of Fe tablets by p < 0.003. The e-ANC instigated a decline in reproductive health problems before (73.4%) and after (10.0%) the intervention. CONCLUSION: The lockdown period influences the low antenatal visits of pregnant women. However, e-ANC for midwives and pregnant women is developed as an alternative solution to improve ANC (i.e., counseling, high-risk early detection, and monitoring Hb and Fe tablets). This consequently has an effect on the reduced reproductive health problems of pregnant women during the pandemic.